MANAJEMEN BUMDES AMANAH DALAM PEMBERDAYAAN MASYARAKAT DI DESA TANJUNG HARAPAN KECAMATAN SINGKEP KABUPATEN LINGGA TAHUN 2022-2024 - Oktapri, Muhammad Isra; Pane, Rico Purnawandi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The Amanah Village-Owned Enterprise (BUMDes) in Tanjung Harapan Village, Singkep District, Lingga Regency, was established as an effort to encourage community empowerment and improve the village economy through the utilization of local potential. However, in its implementation, BUMDes management has not been optimal, characterized by an imbalance between potential and achievement, as well as a decline in performance following the pandemic and changes in management. This study aims to analyze the management of Amanah BUMDes in empowering village communities. The theory used is George Terry's management theory (in Syafiie, 2011), which covers four management functions: planning, organizing, implementing, and monitoring. This research approach uses a descriptive qualitative method, with data collection techniques through interviews and documentation of BUMDes management, village government, and the community. The results show that in general, the management of Amanah BUMDes has been running quite well but not optimally. The planning function has been implemented through business programs such as digital printing and ecoprint batik training, but has not yet reached its full potential for tourism. The organization is structured, but lacks strong continuity among management. The implementation of business activities shows high community participation, but consistency of activities has not been maintained due to limited capital and resources. While the supervisory function is being implemented, it is still not optimal and remains administrative in nature. This study recommends strengthening managerial functions and cross-actor collaboration to achieve sustainable community empowerment through the management of Village-Owned Enterprises (BUMDes). Keywords: Management, Village-Owned Enterprises, Community Empowerment